Alla riscoperta del De otio: una nota sulle lacune e una sul dedicatario, con recensio completa dei manoscritti (De vita beata e De otio) - Malaspina, Ermanno; Giurlanda, Ludovico (Lucius Annaeus Seneca, 2025)
This article begins by outlining the history of the critical text of Seneca’s De otio, then focusing on the problem of the initial and final gaps (only the first one is certain in our opinion) and on the name of the addressee. The hypothesis is put forward that the De otio may also conceal the elaboration of a text originally circulating in the form of a letter. As for the addressee, forgotten nineteenth-century statements are recovered which prove that the index of A presented the name of Annaeus Serenus. The paper then gives an overview of all traceable manuscripts containing both De vita beata and De otio, with a codicological description briefly summarising the physical characteristics and the history of each, and, if already attested, the relationships with other witnesses. Finally, a table facilitates the identification of the manuscripts examined.